Effects of oxygen flow ratio and thermal annealing on defect evolution of aluminum doped zinc oxide thin films by reactive DC magnetron sputtering. (3rd September 2021) - Liu, Chao Ping; Li, Zhan Hua; Egbo, Kingsley O; Kwok, Cheuk Kai; Lv, Xiao Hu; Ho, Chun Yuen; Wang, Ying; Yu, Kin Man
Abstract: Al doped ZnO (AZO) is a promising transparent conducting oxide to replace the expensive Sn doped In2 O3 (ITO). Understanding the formation and evolution of defects in AZO is essential for its further improvement. Here, we synthesize transparent conducting AZO thin films by reactive DC magnetron sputtering. The effects of oxygen flow ratio as well as the rapid thermal annealing (RTA) in different conditions on their structural and optoelectrical properties were investigated by a variety of analytical techniques. We find that AZO thin films grown in O-rich conditions exhibit inferior optoelectrical performance as compared with those grown in Zn-rich conditions, possibly due to the formation of excessive native acceptor defects and/or secondary phases (e.g. Al2 O3 ). Temperature-dependent Hall measurements indicate that mobilities of these highly degenerate AZO films with N > 10 20  cm −3 are primarily limited by ionized and neutral impurities, while films with relatively low N ∼ 10 19  cm −3 exhibit a temperature-activated mobility owing to the grain-barrier scattering. As N increases, the optical band gap of AZO thin film increases as a result of Burstein–Moss shift and band gap narrowing. RTA treatments under appropriate conditions (i.e. at 500 °C for 60 s in Ar) can further improve the electrical properties of AZO thin film, with low resistivity of ∼6.2 × 10 −4 Ω cm achieved, while RTA at high temperature with longer time can lead to the formation of substantial sub-gap defect states and thus lowers the electron mobility. X-ray photoelectron spectroscopy provides further evidence on the variation of Al (Zn) content at the surface of AZO thin films with different processing conditions.